IDENTIFIKASI KARAKTER MORFOLOGI NEMATODA SISTA PADA TANAMAN JAGUNG (Heterodera zeae) DI INDONESIA - Yuliantoro Baliadi (The East Java Biological Society, 2008)
Identification of nematode species is the first step in the resolution of major nematological problems. Accurate identification of maize cyst nematode species is essential for more detailed research, particularly for it control measure. Although morphological observations by using the key characters of each nematode are suitable for identification purposes, the cyst nematodes could not be clearly identified based on it due to the wide variations. For the identification of the cyst nematode species, key characters relating to body surface, head, mouth, esophagus, tail as well as habitat and feeding habits was used in the present examination. Procedures for the permanent and temporary preparations of nematodes were used. The nematode specimens were observed under the microscope to confirm the key characters. Results of measurements and descriptions revealed that the cyst nematode collected from maize roots in Madura island have the same ambifenestrate as that of Heterodera zeae. The underbridge is short and thin and there is two layer of bullae arrangement in vulval cone, the first layer with four finger-like bullae located immediately below the underbridge and the second layer very randomly located below the first one. These characteristics are of H. zeae. These complete of morphological identifications are a new report of H. zeae in Indonesia.